RELEVANSI NILAI KONSERVATISME BESERTA BEBERAPA FAKTOR YANG MEMPENGARUIII - Etty Murwaningsari; Ardhy Puma Caesa Nugraha (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2010)
The objective of this research is to examine the effect of ownership structure, debt covenant, political cost, growth, and earning management on conservatism, and to examine their effect on thefirm's market value. This research uses secondary data obtained from purposive random sampling. The data sample consists of 50 manufacturing firm between the year 2005-2007. However, from the outlier test, only 103 firm-year can be processedfurther using Structural Equation Model (SEM). This research results suggest that there is a significant effect of earning management on conservatism. Whilst ownership structure, debt covenant, political cost, and growth don't seem to have significant effects on conservatism. There is also no significant relationship between conservatism andfirm's market value.